Religiusitas Prajurit sebagai Integrasi Keberagamaan dengan Nasionalisme pada Pendidikan dan Latihan Pasukan Khusus - Dyah Salsabil (UIN Sunan Gunung Djati Bandung, 2021)
The phenomenon of religious cultivation and development in the Batujajar Special Forces Education and Training Center, West Bandung Regency, is interesting if it is associated with nationalism. This article aims to dig deeper into the theological domain or the religious orientation of the military in terms of the military perspective as a state defense system and from the military point of view as a community system. This research is qualitative research with theological, sociological and psychological approaches. Using participant observation techniques, interviews (structured and unstructured), and documentation, this research concludes that the diversity of Komando 104 Students has its characteristics. Namely, they state that religion legitimizes the values and norms of the enactment of the Soldier's Oath, 8 Mandatory TNI, Sapta Marga, and Command Soldiers' Promise. They adhere to the principle of nationalism so that they are obliged to be neutral, both when on duty, in politics and even in their religion. The nationalist religious orientation is a picture of religion that prioritizes unity and integrity so that it is easily accepted by all circles. This study can provide a roadmap for forming patterns of education and training in government organs within the framework of religion and nationalism.